Act of Feb 16, 1899, ch. 4, § 28, W.Va. Acts 14, 24. - (:unkn) unknown (My University, 1899)
to regulate the keeping of gun powder and other inflammable or dangerous substances; to provide for the regular building of houses or other structures
Keywords: GUNPOWDER - STORAGE